“The Gems of Water”: a co-created scientist-citizen approach for water quality monitoring - Cacciatori, Caterina; Mariani, Giulio; Comero, Sara; Marin, Daniela; Cabrera, Maria; Bon-Tavarnese, Jennifer; Gaggstatter, Joel; Tavazzi, Simona; Maffettone, Roberta; Myers, Jackie; Pettigrove, Vincent; Gawlik, Bernd Manfred (Frontiers in Water, 2024)
To better understand local water quality pollution by organic contaminants and how it affects communities around the world, “The Gems of Water” project aims to build a co-creative global scientist-citizen approach, actively engaging citizens and connecting them to scientists and to advanced water monitoring tools. The project applies the Stir Bar Sorptive Extraction technique with an advanced wide-screening method, used to assess the occurrence of agrochemicals, industrial compounds and pharmaceuticals in surface and groundwaters. In collaboration between Coral Conservation and the Joint Research Centre (JRC) of the European Commission, a study was conducted to identify contamination patterns which could be affecting the coral reef by investigating water quality in local rivers in the south Caribbean region of Costa Rica, an area characterized by agricultural activities linked to bananas production. Coral Conservation is a youth-led non-governmental organization focused on activities for the conservation and protection of the coral reef. Sampling locations for the study were jointly determined with members of the Coral Conservation group and included 13 sampling points from 3 different rivers and 2 wells. The pilot study allowed evaluation of the workflow for scientist-citizen collection of water quality data, whereby participants from the local community conduct sampling and extraction activities, while the wide-screening analysis of about 230 contaminants is performed at the JRC Water Laboratory. Considering the lessons learned through the Costa Rican pilot case, in this paper we discuss the elements required for successful scientist-citizen projects. Challenges are described and outlooks provided to improve citizens’ engagement projects and others participatory water quality monitoring activities. “The Gems of Water” project contributes to data collection of rarely monitored compounds in rural and remote areas through a scientist-citizen approach, addressing knowledge gaps on water quality and building bridges between science and society. The outlook is for such an innovative approach to support bottom-up management actions which can lead to alternative solutions in water quality management.